The development of a decision support system for the infant food chain - Brian Flynn; Rallou Thomopoulos (Elsevier, 2022)
Summary: In a time where the awareness of food safety and quality increases among the general population, it is vital that consumers are enabled to make informed decisions on risks involving the safety of their food. The SAFFI (Safe Food for Infants in EU and China) project aims to build an integrated decision support system (DSS) for the infant food chain that will enable stakeholders at all levels to make informed decisions regarding infant food. The infant food chain was selected due to its strict regulatory requirements, its vulnerabilities as highlighted by different food safety crises, the economic importance of the infant food sector in the EU and China and the focus on this particular food chain by food safety authorities.The SAFFI project will incorporate data and models from work packages dealing with hazard identification (HI), hazard detection (HD), hazard control (HC) and risk ranking (RR). The models will be integrated into a user-friendly and upgradeable cloud-based decision support system application. A multi-actor cost-benefit analysis of the project will be carried out, enabling the stakeholders in the project to assess the relevance of implementing the project technologies by integrating food safety, regulatory and economic criteria.The decision support system will be validated on four specific case studies, and tested on end-users, with the aim of extending this approach to other food chains.